Formação de professores (as) ruralistas em Juazeiro do Norte (CE) 1934-1973: um projeto emancipatório - Barros, Pedro Ferreira (2011)
The objective of this work is to know as the received formation of the Rural Normal School of Juazeiro - ENRJ contributed to the conquest of e mancipation spaces for former-students in your life paths, to identify educational and cultural practices used, that they can illuminate the process of education of the present generations contributing to the elaboration of public politics. For this end the period from 1934 to 1973 , was focused time during which the project of rural teachers' formation was executed. The research of qualitative nature was developed in the descriptive and explanatory levels as study of partner-anthropological and historical character, in an approach fenomenológical in the perspective of the etnometodologia. The subject of the research were teachers formed by ENRJ. In the execution of the field work they were picked through interviews semi-structured five reports histories of former-students' life formed in the years of 1938, 1942, 1950 and 1959, narrating memoirs of your existences in the family, ranches, city, school and professional practices, the ones which, as results of the research they were analyzed in response to the central question that relates Formation and emancipation. Sources of other natures were used as : school registrations, speeches of authorities, teachers and students, and the source hemerográfica. In the theoretical-methodological course the oralidade is detached as important research source. It is placed, for this middle, in the pulp of the from Ceará education nal history of middles of the Century XX, the woman, the educator, the teacher elementary school teacher, your formation ruralist in Juazeiro of the North and the subject of your emancipation for the education and for the work.